Research on the Efficiency of Complex Fertilizer Produced from the New Serpentine-Based Ingredient - Yeritsyan, Sergey; Gasparian, Gayane; Grigoryan, Karen; Khachatryan, Anna (ՀԱԱՀ հիմնադրամ)
Using serpentine, which is widespread in Armenia, we developed two new fertilizers. First fertilizer, is composed of phosphorus, calcium, magnesium, and sulfur, as well as amorphous silicon dioxide, and fertilizer 2, which contains a small amount of phosphorus (in the form of a mixture in the mineral), calcium, magnesium, sulfur, and amorphous silicon dioxide. Fertilizers were soluble in water and a 1 % ammonium carbonate solution. Laboratory studies have shown that fertilizers positively affect spring barley seed germination percentage, germination rate, growth, yield, and grain NPK content. The yield of spring barley increased by 28.4-33.1 % under the influence of fertilizers, which is equivalent to the efficiency of double superphosphate. However, serpentine, the most common in Armenia, can be used to obtain recommended fertilizers in a much cheaper and safer manner.
Keywords: Agronomy and Agroecology